Hydrologic Response of Sierra Nevada Mixed-Conifer Headwater Catchments to Vegetation Treatments and Wildfire in a Warming Climate - Saksa, Phil C.; Conklin, Martha H.; Tague, Christina L.; Bales, Roger C. (Frontiers in Forests and Global Change, 2020)
We used a hydro-ecologic model (RHESSys) constrained by measurements of stream discharge, and spatially distributed snow and soil moisture, to simulate the impacts of operational forest treatments, historical wildfire and climate warming on productive mixed-conifer forests. We compared the response of two headwater catchments at the rain-snow-transition elevation in the wetter central Sierra and more water-limited southern Sierra. The variability of precipitation exerted a greater influence on annual evapotranspiration and runoff than vegetation changes from operational fuels treatment or historical wildfire. The short-term impacts of vegetation changes associated with wildfire, however, did have a greater effect on evapotranspiration and runoff than temperature increases in a warming climate. The average central-Sierra headwater response of evapotranspiration and runoff to fuels treatments (−12%, +12%, respectively) and wildfire (−43%, +46%) were greater than the projected responses to a 4.5°C temperature increase (+2 and −7%). The response in the southern Sierra was limited by lower annual precipitation and showed no response to fuels treatments; but the catchment showed respective changes of −11 and +17% in evapotranspiration and runoff for wildfire, versus +9 and −3% to a 4.5°C temperature increase. These results suggest that in the central Sierra, reductions in vegetation from either fuels treatments or historical wildfire can, temporarily, offset reductions in streamflow from a warming climate. In the southern Sierra, impacts of fuels treatments were small, and only more-extensive vegetation removal as would occur with wildfire, results in significant changes in hydrologic fluxes. Further research is needed to investigate how initial hydrologic changes and climate effects evolve as vegetation adapts and regrows following disturbance.